Autochthonous leprosy in Spain: Has the transmission of Mycobacterium leprae stopped? - Inés Suárez-García; Diana Gómez-Barroso; Paul E M Fine (Public Library of Science (PLoS), 2020)
Background The aim of this study is to explore whether transmission of M. leprae has ceased in Spain, based upon the patterns and trends of notified cases. Methodology Data on new cases reported to the National Leprosy Registry between the years 2003-2018 were extracted. In absence of detailed travel history, cases were considered "autochthonous" or "imported" based on whether they were born within or outside of Spain. These data were analyzed by age, sex, clinical type, country of origin, and location of residence at time of notification. Principal findings Data were available on 61 autochthonous and 199 imported cases since 2003. There were clear declines in incidence in both groups, and more imported than autochthonous cases every year since 2006. Autochthonous cases were more frequently multibacillary and had older age at diagnosis compared to imported cases. All the autochthonous cases had been born before 1985 and were more than 25 years old at diagnosis. Male-to-female ratio increased with time for autochthonous cases (except for the last time period). The imported cases originated from 25 countries, half of them from Brasil and Paraguay. Autochthonous cases were mainly distributed in the traditionally endemic regions, especially Andalucía and the eastern Mediterranean coast. Conclusions Autochthonous and imported cases have different epidemiologic patterns in Spain. There was a clear decline in incidence rates of autochthonous disease, and patterns consistent with those reported from other regions where transmission has ceased. Autochthonous transmission of M. leprae is likely to have now effectively stopped in Spain.